2020
DOI: 10.3389/fneur.2020.00076
|View full text |Cite
|
Sign up to set email alerts
|

Defective Gating and Proteostasis of Human ClC-1 Chloride Channel: Molecular Pathophysiology of Myotonia Congenita

Abstract: The voltage-dependent ClC-1 chloride channel, whose open probability increases with membrane potential depolarization, belongs to the superfamily of CLC channels/transporters. ClC-1 is almost exclusively expressed in skeletal muscles and is essential for stabilizing the excitability of muscle membranes. Elucidation of the molecular structures of human ClC-1 and several CLC homologs provides important insight to the gating and ion permeation mechanisms of this chloride channel. Mutations in the human CLCN1 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 201 publications
(303 reference statements)
0
19
0
Order By: Relevance
“…For example, in direct contrast to the universally expressed hyperpolarization-activated ClC-2 channel, the ClC-1 channel is specifically expressed in skeletal muscles and activated by membrane depolarization. Loss-of-function mutations in the human CLCN1 gene that instigate defective gating and proteostasis of the ClC-1 channel have been associated with the hereditary muscle disease myotonia congenita [ 5 , 63 ]. Interestingly, we previously demonstrated that ClC-1 WT and disease-causing mutant proteins are also subject to polyubiquitination and degradation by the CUL4-DDB1-CRBN E3 ubiquitin ligase [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in direct contrast to the universally expressed hyperpolarization-activated ClC-2 channel, the ClC-1 channel is specifically expressed in skeletal muscles and activated by membrane depolarization. Loss-of-function mutations in the human CLCN1 gene that instigate defective gating and proteostasis of the ClC-1 channel have been associated with the hereditary muscle disease myotonia congenita [ 5 , 63 ]. Interestingly, we previously demonstrated that ClC-1 WT and disease-causing mutant proteins are also subject to polyubiquitination and degradation by the CUL4-DDB1-CRBN E3 ubiquitin ligase [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mutations of ClC-1 associated with myotonia congenita can be correlated to anomalous gating-permeation or reduced ClC-1 protein abundance at the plasma membrane (Lee et al, 2013;Jeng et al, 2020). This distinction, together with the new and important advance in knowledge of the mechanisms behind proteostasis (Peng et al, 2016), biogenesis (Chen et al, 2015) and those governing trafficking to the surface membrane (Peng et al, 2018), has opened the doors to the novel pharmacological approach for increasing ClC-1 in plasma membrane (Altamura et al, 2018;Jeng et al, 2020). By studying the biophysical mechanism to induce an increase of ClC-1 in plasma membrane, certain inhibitors of ligase E3 (Lee et al, 2013) or blockers of ubiquitin inhibitors (Chen et al, 2015) are emerging.…”
Section: Discussionmentioning
confidence: 99%
“…CD modeling comparisons here highlight two overlooked facets of SMF physiology: 1) the collaboration of ClC-1 channels with Donnan effectors is imperative for SMF ion homeostasis (not just for low SMF excitability (Jentsch and Pusch, 2018; Jeng et al 2020) and 2) the extraordinary smallness of the (unidentified) SMF P Na renders it pivotal (via its [small I Naleak ]) to the robustness of SMF ion homeostasis.…”
Section: Introductionmentioning
confidence: 96%